SELF-TRUST IN CONNECTION WITH EMPATHY IN DIFFERENT SOCIAL SITUATIONS OF DEVELOPMENT IN ADOLESCENCE - Danilova, Yulia (PSYCHOLOGICAL JOURNAL, 2019)
The article analyzes the level of self-trust in connection with empathy intensity level in different social situations of development in adolescence. Characteristics of self-trust in important spheres of life and empathy towards different categories of people in adolescents, living in complete and incomplete families, and also in orphanages were studied. The sample: 286 adolescents from Saint-Petersburg, Russia, aged 14-16 (126 boys;160 girls), including 97 orphanage teenagers (46 boys; 51 girls), 104 full families children (53 boys; 51 girls); 85 single-parent families children (40 boys; 45 girls). Self-trust survey by T.P.Skripkina was used to investigate self-trust level in significant spheres of life in adolescents. Empathy diagnostics by I.M.Yusupov was used to measure empathy level toward different people in adolescents. Data analyses included descriptive statistics analysis, Student's t-test, correlation analysis by Spirmen.Results of our study indicate, that self-trust in adolescence is not equally manifested in various spheres of life. Self-trust is expressed less in problematic areas: educational and relations with the opposite sex. Self-trust in the areas of relationships with peers and a family is expressed at the highest level. Social situation of development influences on self-trust: adolescents from full families, all indicators of self-trust are higher. The focus of empathy also varies among adolescents from full families and those who have experienced trauma of parting with parents. The findings showed the importance of not only the presence, but also the composition of the family for successful emotional development in adolescence.